Since you asked... - Goo, Maurene (Scholastic Press, 2013)
Fifteen-year-old Holly Kim, the copyeditor for her San Diego high school's newspaper, accidentally submits a piece ripping everyone to shreds and suddenly finds herself the center of unwanted attention--but when the teacher in charge of the paper asks her to write a regular column her troubles really start.